From Mind to Soul : A Bibliometric Analysis of IQ, EQ, and SQ in Aca-demic Research - Ana Sofia Herawati; Siti Mardah; Aida Vitria; Gusti Meinar Girda Ariani; Nurul Hasanah; Lamsah Lamsah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to present a comprehensive bibliometric analysis of Intellectual Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ) in an academic context, particularly focusing on the role of lecturers. Using bibliometric methods. The data for this study came from 300 English-language scientific articles published in 2023 from the Scopus and Google Scholar databases. The analysis was carried out using keyword co-occurrence techniques, overlay visualization, density visualization, and author collaboration networks. The findings show that there is a strong focus on developing conceptual frameworks and reviewing literature related to IQ, EQ, and SQ, indicating an effort to understand the integration of these three intelligences as the foundation for human resource development in higher education. However, several keywords were also found to be thematically irrelevant, suggesting challenges in data filtering or uniqueness of terminology between disciplines. Collaborative networks between authors tend to be fragmented, indicating the potential for fostering broader collaboration. The implications of this study theoretically reinforce the need for the integration of IQ, EQ, and SQ in understanding holistic intelligence, while practically encouraging higher education institutions to design lecturer development programs that balance these three aspects of intelligence to form superior character and performance